The Reflection Of Interreligious Tolerance Ideas In The Work “Kitab At-Tawhid” - Zarifjon Gulomov (Indonesian Journal Publisher, 2025)
This article is dedicated to studying the ideas of interreligious tolerance presented in Abu Mansur al-Maturidi's Kitab at-Tawhid. The work extensively elaborates on principles such as human dignity, freedom of choice, mutual understanding and dialogue, as well as respect for other religions. These principles remain relevant not only historically but also in the context of contemporary globalization and multicultural societies. Additionally, this article analyzes modern scholars' reflections on Imam Maturidi's ideas of tolerance, highlighting their significance in contemporary interreligious dialogue